1982
DOI: 10.1007/bf01011896
|View full text |Cite
|
Sign up to set email alerts
|

A histological method for the visualization of the intercellular permeability barrier in mammalian stratified squamous epithelia

Abstract: Mammalian epidermis and oral epithelial possess an intercellular permeability barrier which is located in the superficial region of the tissue. This study reports a staining reaction which appears to demonstrate a histological correlate of this functional property. Specimens of ear skin, palate, buccal and oesophageal mucosa and of cornea and bladder were obtained from adult rabbits and rats, bisected and either incubated in vitro with 2.5% horseradish peroxidase as a tracer or fixed and processed for light mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…MCG have also been found in esophageal epithelium 12. Their appearance and localization is similar to that in the buccal mucosa and the secreted material has been correlated to the performance of the permeability barrier 13,14…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…MCG have also been found in esophageal epithelium 12. Their appearance and localization is similar to that in the buccal mucosa and the secreted material has been correlated to the performance of the permeability barrier 13,14…”
Section: Introductionmentioning
confidence: 85%
“…Similarly, they first appear in the prickle‐cell layer and they subsequently fuse with the plasma membrane and secrete their content in the intercellular space. This intercellular material is related to the permeability barrier: the penetration of horseradish peroxidase across rabbit buccal and esophageal epithelium was blocked at the level of MCG secretion 13,22. That having been said, the composition of the esophageal intercellular material is not well‐known, although glycoconjugates similar to those in the buccal mucosa have been found 21.…”
Section: Discussionmentioning
confidence: 99%
“…Hill et al (1982) also observed the uptake of HRP by rabbit bladder epithelium. They treated small pieces of dissected bladder tissue (1-2 mm cubes) with HRP, but they did not describe the precise distribution of HRP within the epithelium.…”
Section: Discussionmentioning
confidence: 85%